2020
DOI: 10.1177/0956797620966526
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Being Lured Away by a Stranger: A Real-World Field Test of Selective Trust in Early Childhood

Abstract: In this preregistered field study, we examined preschool children’s selective trust in a real-life situation. We investigated whether 3- to 6-year-old children (total N = 240) could be lured to a new location within their school grounds by an unfamiliar adult confederate. In a between-subjects manipulation, the confederate established either a high or a low level of personal credibility by providing information that the child knew to be either true or false. In Experiment 1, in which the confederate was female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Any of these specific factors could have affected the results. For example, the gender and age of the partner might have played a role in the generalizations participants made, as is suggested by evidence that men tend to be viewed as more threatening than women (Li et al., 2020) and that preschool‐age children tend to prefer to play with same‐age peers (Shutts et al., 2010). The accent of the game partner (Kinzler et al., 2009) as well as the specific ingroups and outgroups in question (Birtel et al., 2019; Qian et al., 2017) might have played a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…Any of these specific factors could have affected the results. For example, the gender and age of the partner might have played a role in the generalizations participants made, as is suggested by evidence that men tend to be viewed as more threatening than women (Li et al., 2020) and that preschool‐age children tend to prefer to play with same‐age peers (Shutts et al., 2010). The accent of the game partner (Kinzler et al., 2009) as well as the specific ingroups and outgroups in question (Birtel et al., 2019; Qian et al., 2017) might have played a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting for future research to extend the current aims to other social settings that do not involve a transactional decision, such as how children trust teachers, their friends' parents, or individuals they interact with online. Recently, in a field study assessing children's susceptibility CHILDREN'S USE OF CUES IN ECONOMIC TRUST GAME 9 to being lured away by strangers, Li et al (2020) found that, alarmingly, about half of their preschool-aged child participants left the playground with a confederate in the study. However, children were less likely to be lured away by an adult who provided inaccurate and unreliable information (Li et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Recently, in a field study assessing children's susceptibility CHILDREN'S USE OF CUES IN ECONOMIC TRUST GAME 9 to being lured away by strangers, Li et al (2020) found that, alarmingly, about half of their preschool-aged child participants left the playground with a confederate in the study. However, children were less likely to be lured away by an adult who provided inaccurate and unreliable information (Li et al, 2020). While Li and colleagues examined children's trust in strangers based on reputational information, they did not examine the possible influence of facial trustworthiness on children's trust in these strangers.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For example, it is possible that inconsistency matters less in contexts where target and behavior valence is unambiguously negative (so there is no attempt to assess or build trust). It will also be important to examine the extent to which the present account applies to different forms of trust, including epistemic trust (Koenig & Harris, 2007) and interpersonal trust (Fu et al, 2015;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%